Homoepitaxial lateral growth of single-crystal diamond with eliminating PCD rim and enlarging surface area. (March 2022) - Cao, Wei; Ma, Zhibin; Gao, Deng; Fu, Qiuming; Zhao, Hongyang
Abstract: Avoiding the appearance of polycrystalline diamond (PCD) rim during the epitaxial lateral outward growth of single-crystal diamond (SCD) by microwave plasma chemical vapor deposition (MPCVD) is still full of difficulties and challenges. Herein, the enlarged SCD without PCD rim was synthesized via different growth modes. The core strategy is the self-formation of off-angles on (001) crystal face by regulating the radicals distribution and reducing the temperature at the seed edge. Therefore, the appearance of the secondary nucleation at the edge regions can be inhibited. In a dual-substrate reactor, the SCD surface displayed a typical terrace flow growth pattern. The growth steps on the SCD surface are directed from the center to the edge which coincides with the distribution of carbon-related radicals and temperature. In addition, a spiral growth mode appeared in the homoepitaxial growth of SCD by a single-substrate reactor. Under a spiral growth mode, the top surface of SCD in an off-axis direction was contributed to form a smooth interface. The SCD surface increased by 88.15% from 3 × 3 mm 2 to 4.11 × 4.12 mm 2 after 82 h. And the crystalline quality of the CVD epitaxial layer is higher than that of the type Ib seed. Graphical abstract: On a semi-open holder, single-crystal diamond (SCD) without polycrystalline diamond (PCD) rim has laterally grown under different growth modes by self-forming the off-angles on the top surface. The surface area of the SCD enlarged from 3 mm × 3 mm–4.11 mm × 4.12 mm under a spiral growth mode. Both the top surface and lateral surface display a single-crystal growth pattern. Image 1 Highlights: The terrace-flow growth mode and spiral growth mode are suitable for expanding the top surface of single-crystal diamond. The top surface area of SCD has increased to 1.88 times than the original by the spiral growth mode. On a semi-open holder, the distribution of plasma and temperature can be regulated to eliminate polycrystalline diamond rim.